STRENGTH DETERMINATION OF SUPPORT STRUCTURES OF OPEN-TOP CAR WHEN TRANSPORTING BY TRAIN FERRY (Transport systems and technologies, 2018)
The article presents the strength research results of the improved structure of the open-top car of bodywork during transportation on the railway ferry. The peculiarity of the car is the presence of nodes for fastening chain screeds in its supporting structure. In order to determine the dynamic loads that effects the car body during transportation on the railway ferry, a mathematical model of displacements has been created. The model takes into account the angular movement of the railway ferry with cars in relation to the longitudinal axis (roll), as a case of the most unfavorable loading of the body structure, as well as ensuring its stability in relation to the deck. When determining the dynamic loading of the car body, the randomness of the parameters of the disturbing action (sea wave) was taken into account. The solution of the mathematical model was carried out in the software environment MATHCAD. For taking into account the variables of the disturbing influence, the theory of Fourier series was used. The resulting accelerations, as components of the dynamic load effecting the body of the car, are taken into account in the research of strength. The calculation was carried out using the finite element method. It is established that the maximum equivalent voltage does not exceed the permissible voltage. The studies will contribute to improving the combined transport functioning efficiency through international transport corridors, as well as strengthening the economic position of Ukraine in the international market of transport services.
Keywords: open-top car, supporting structure, modeling, dynamic loading, strength, rail-ferry transportation.